2000
DOI: 10.1111/j.1365-277x.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing low uptake of periconceptional folate warrants increased food fortification

Abstract: Correspondence 4 Wexham Lodge,Objective To assess whether the Health Education Authority's recent promotion of periconceptional folic acid has been successful in increasing uptake sufficient to prevent neural tube defects.Design A retrospective questionnaire, completed by 162 patients in the early pregnancy clinic in Doncaster Royal Infirmary, an averagesized UK district general hospital. The study ran in February and March 1999.Methods and main outcome measures Data were collected on: supplementation and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Only 16% of participants claimed to have no knowledge of folic acid. These results are analogous to a previous UK study (Sillender, 2000) where only 19% of participants had no knowledge of folic acid. It is clear that, although knowledge of the requirement for folic acid periconception is high, its use is consistently low and shows no sign of improving.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Only 16% of participants claimed to have no knowledge of folic acid. These results are analogous to a previous UK study (Sillender, 2000) where only 19% of participants had no knowledge of folic acid. It is clear that, although knowledge of the requirement for folic acid periconception is high, its use is consistently low and shows no sign of improving.…”
Section: Discussionsupporting
confidence: 88%
“…More recent studies have shown that preconception use of folic acid remains low (24–31%) and, although postconception use is higher (63–83%), it is thought that many women do not begin until after neural tube closure (Mathews et al. , 1998; Sillender, 2000; Brooke & Doyle, 2001).…”
Section: Introductionmentioning
confidence: 99%